The Impact of Slang on The Indonesian Language Skills of Politeknik Negeri Medan D-3 Accounting Students - Sulaiman Ahmad; Syahrudin Marpaung; Tosanov Tohap Parulian Napitupulu (Journal of Social Science, 2022)
Indonesian as a national language must be preserved. The development of slang can threaten Indonesian if the user does not have a love of his own country's language. Slang can undermine the existence of Indonesian among the people. This study aims to explain how much influence the use of slang by adolescents has on Indonesian language skills under the rules. The explanation was obtained from the analysis and observation carried out carefully. Observations are based on the use of language in communication, the delivery of ideas or ideas both verbally and in writing, and other social relationships in interacting in public places. Indonesian use among students in its development has begun to be displaced by slang. Mixing slang with standard language creates a problem or oddity in language. The use of slang does not matter when relying on the nuances of familiarity it evokes. However, it would be nice if a person still had to know the limits to prevent an adverse impact on preserving the Indonesian language. This study uses a qualitative descriptive approach by trying to skin social phenomena in an atmosphere occurring naturally without any other control.